Special foods and local herbs used to enhance breastmilk production in Ghana: rate of use and beliefs of efficacy - Zakari Ali; Mohammed Bukari; Anita Mwinisonaam; Abdul-Latif; Abdul-Razak Abizari (BMC, 2020)
Abstract Background Inadequate breastmilk production is one of the key factors associated with suboptimal breastfeeding. In most local African homes, special herbs and some food items are commonly used to promote breastmilk production (known as lactogogue/galactogogue). We describe the use and characterize the herbs and food items used to promote breastmilk production in two regions of Ghana. Methods We conducted a cross-sectional study in 2018 involving 402 lactating mothers. The range of foods used as lactogogues was obtained from 20 participants through focus group discussions. Quantitative data on demographics, lactogogue use and feeding practices were obtained through questionnaire administration. Results The mean age of women was 29.2 years and children were 10 months. Breastmilk production problems were low (22.4%) and the majority of lactating mothers felt they had adequate breastmilk (70.4%) but awareness about lactogogues was widespread in both regions (88.8%) and highest in the Brong-Ahafo region (90.0%). Information about lactogogues was mainly from grandparents (24.6%), parents (31.6), health facilities (16.5%) and friends (12.8%), while the media had little influence (< 1%). The majority of the mothers used lactogogues to enhance breastmilk production (67.7%), and a quarter of them used lactogogues because of their tradition (25.2%). Prevalence of lactogogue use was 83.8%, lactogogues were prepared separate from household meals (59.4%) and consumed one to three times a day (89.6%). Users felt the effectiveness within 24 h of use (98.5%). The most common lactogogues included; groundnut/peanut soup prepared with Bra leaves (Hibiscus sabdariffa), hot black tea, Werewere/Agushi (Citrulus colocynthis) prepared with Bra leaves, and Abemudro (a polyherbal formulation). Only 13.2% of lactating mothers also used lactogogues during pregnancy. Conclusions Special foods and selected herbs are widely used to enhance breastmilk production in Ghana and constitute an important part of the diet of lactating mothers. These results could contribute to understanding breastfeeding behaviours and stimulate further research into evaluating the safety and scientific efficacy of these products in Ghana.